(untitled) (Research, Society and Development, 2023)
Objective: To theoretically describe the main factors of Minority Stress related to the manifestation of the depressive state in LGB individuals through a narrative review, based on psychiatric conceptions about depression. Methodology: A narrative review of recent literature, including free articles from the last 05 years (from 2018 to 2022) found from a search on online platforms. For the choice of method, the scope made possible for the theoretical discussion of the theme was considered. Results and discussions: MS is a component of the etiology of the depressive state. MS factors are related to family relationships, internalized homophobia, discrimination, and stigma, and predict depressive symptoms such as sadness and suicidal ideation. They are also part of a bad relationship with religiosity, a hostile political atmosphere, and intersectionality. Community connectivity, disclosure of sexual orientation, family acceptance, and redefinition of spirituality act as psychoprotectors and as sources of hope and peace, preventing the impoverishment of social relationships. Conclusion: quantitative and qualitative studies on the subject are rare, especially in Brazil. However, the debate on the subject is necessary and should be expanded. The community of health professionals should benefit from the discussions, to update knowledge, and reach a humanitarian and compassion-based form of care.